2015
DOI: 10.1007/s13197-015-2088-5
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic fingerprint of tea varieties by surface enhanced Raman spectroscopy

Abstract: The fingerprinting method is generally performed to determine specific molecules or the behavior of specific molecular bonds in the desired sample content. A novel, robust and simple method based on surface enhanced Raman spectroscopy (SERS) was developed to obtain the full spectrum of tea varieties for detection of the purity of the samples based on the type of processing and cultivation. For this purpose, the fingerprint of seven different varieties of tea samples (herbal tea (rose hip, chamomile, linden, gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 39 publications
(51 reference statements)
0
13
0
Order By: Relevance
“…Shaw et al (2007), reported about the colour changes occurring during drying of most of the leaves using microwave drying process. There is increasing need for methods and tools for determining the characteristics of tea varieties (Buyukgoz et al, 2016). 6.67 ± 0.00 a 6.67 ± 0.01 a 6.67 ± 0.02 a 6.67 ± 0.03 a 7.78 ± 1.92 a 6.67 ± 0.03 a pH 5.89 ± 0.02 d 6.25 ± 0.02 a 6.06 ± 0.09 b 5.98 ± 0.01 c 5.96 ± 0.03 cd 5.97 ± 0.01 cd Mean scores in the same row with different superscripts are significantly different (p < 0.05).…”
Section: Overall Acceptabilitymentioning
confidence: 99%
“…Shaw et al (2007), reported about the colour changes occurring during drying of most of the leaves using microwave drying process. There is increasing need for methods and tools for determining the characteristics of tea varieties (Buyukgoz et al, 2016). 6.67 ± 0.00 a 6.67 ± 0.01 a 6.67 ± 0.02 a 6.67 ± 0.03 a 7.78 ± 1.92 a 6.67 ± 0.03 a pH 5.89 ± 0.02 d 6.25 ± 0.02 a 6.06 ± 0.09 b 5.98 ± 0.01 c 5.96 ± 0.03 cd 5.97 ± 0.01 cd Mean scores in the same row with different superscripts are significantly different (p < 0.05).…”
Section: Overall Acceptabilitymentioning
confidence: 99%
“…On the other hand, PCA through analysis of variance produced much lower accuracy for the strains with both linear discrimination analysis (72.7%) and linear SVM classification (68.2%). In addition to different beverages (Mandrile et al., 2016; Mendes et al., 2003; Nordon et al., 2005; Pierna et al., 2012; Silveira Jr et al., 2009; Wu et al., 2015; Zanuttin et al., 2019), the chemometric‐based Raman/SERS approach has also been extended to all sorts of foodstuffs quality monitoring, such as dairy products, (Almeida et al., 2011; Caponigro et al., 2019; de Oliveira Mendes et al., 2019; Júnior et al., 2016; Karunathilaka et al., 2016; Liu et al., 2020; Moros et al., 2007; Nedeljkovic et al., 2017; Nieuwoudt et al., 2017; Richardson et al., 2019; Stefanov et al., 2013; Taylan et al., 2020; Zhao et al., 2020), vegetables (Sebben et al., 2018), wheat, flour (Cebi et al., 2017; Czaja et al., 2016; Liu et al., 2019), tea, and coffee (Buyukgoz et al., 2016; El‐Abassy et al., 2011; Figueir, 2019; Liao & Chen, 2017; Luna et al., 2019). The wide literature indicates the applicability of chemometric algorithms in Raman/SERS‐based quality monitoring of foodstuffs (Table 2).…”
Section: The Applications Of Raman/sers and Chemometrics In Evaluating Food Quality Attributesmentioning
confidence: 99%
“…Data processing method of Principal Component Analysis (PCA) was used to separate tea species and several models for different tea samples. The combined method of fingerprinting-PCA was accurate and rapid for the evaluation of different tea species [ 112 , 113 ].…”
Section: Application On the Detection Of Plant Original Biomoleculmentioning
confidence: 99%